Targeting MALT1 Suppresses the Malignant Progression of Colorectal Cancer via miR-375/miR-365a-3p/NF-κB Axis - Qian, Rui; Niu, Xinli; Wang, Yinghui; Guo, Zhi; Deng, Xuyi; Ding, Zhenhua; Zhou, Meijuan; Deng, Haijun (Frontiers in Cell and Developmental Biology, 2022)
Colorectal cancer (CRC) is a malignant tumor with the second highest morbidity and the third highest mortality in the world, while the therapeutic options of targeted agents remain limited. Here, mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1), known as the upstream of the NF-κB signaling pathway, was identified to be highly upregulated in CRC tumors and cell lines. Furthermore, the downregulation of MALT1 or inhibition of its proteolytic function by MI-2 suppressed the cell proliferation and migration of CRC cells. In vivo, suppressing the MALT1 expression or its proteasome activity effectively reduced the size of the subcutaneous tumor in nude mice. Mechanistically, miR-375 and miR-365a-3p were identified to inhibit NF-κB activation via targeting MALT1. Overall, our results highlight that a novel regulatory axis, miRNA-MALT1-NF-κB, plays a vital role in the progression of CRC and provides novel and hopeful therapeutic targets for clinical treatment.